(untitled) (Journal of Geography and Environmental Management, 2025)
Russia was formed as a multinational state, and the peoples of the Russian North, Siberia, and the Far East entered its sphere of influence. The territories that became part of the Russian state were distinguished not only by the diversity of climate, landscape, and level of economic development, but also by ethnic diversity. The peoples of Russia belonged to different races and language groups, were at different stages of development, and differed in religion and psychology. The role of the unifier of various peoples within one state was played by the Russian people. A special place in the ethnic composition of the Russian Empire was occupied by the Finno-Ugric peoples, who over time became the basis of statehood: Hungarians, Finns, Estonians; national-territorial entities: Karelians, Komi, Komi-Permyaks, Mansi, Mari, Mordvins, Udmurts, Khanty. The paper examines the demographic dynamics of the Finno-Ugric peoples of the Russian Federation based on the materials of the Soviet (1926-1989) and Russian (2002-2021) population censuses; it is noted that the population dynamics had multidirectional dynamics – there were periods of population growth and decline, but the Finno-Ugric peoples suffered the greatest demographic losses in the 21st century – more than 1 million people. The history of the development of the Finno-Ugric peoples is quite fully presented in scientific literature; current problems and development prospects are reflected in constantly held international conferences and world congresses. The article focuses on non-demographic factors, primarily focusing on assimilation processes. The indicators that indirectly or directly affect the assimilation of Finno-Ugric peoples are given: the choice and use of the "mother tongue", preferred residence in the ethnic homeland or in other regions of the federation, the prevalence of interethnic marriages.